Financial System Development and Economic Development in Malawi - Chikafa, Scora (School of Economics, 2023)
The financial system development and economic development nexus has been a debate for over a decade. Both theory and empirical evidence provides conflicting evidence on the direction and nature of the relationship between financial system development and economic development. Results vary widely depending on whether one uses bank-based or market-based indicators of financial development. This paper seeks to address by using the composite indicator of financial development, developed by the International Monetary Fund( IMF), which captures depth, access, and efficiency of the financial system. Using yearly data of the period range 1980 to 2019, and employing an Autoregressive Distributed Lag (ARDL) cointegration technique or bound cointegration technique, the paper finds a significant long run negative relationship between financial system development and economic development, which runs from financial system development to economic development of Malawi. Therefore, in order to improve economic development, Malawi has been advised to improve its financial system through easy credit access and boosting its forex market, improve infrastructure and implement financial literacy programs that would teach citizens how best they can utilize resources given to them.